2009
DOI: 10.2174/1875934300902010049
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Study of Relations Between Prior Knowledge, Comprehension, Disorientation and On-Line Processes in Hypertext

Abstract: An exploratory experiment was carried out in order to question the relationships between prior knowledge, comprehension performance, on-line processes and disorientation in a non-linear document (hypertext). 14 participants read a non-linear document about a virus' infectiousness process which imposed to learners to construct themselves their reading orders and also a structure of the document. Correlational analyses were conducted to test the relations between the variables. Results indicated that the prior k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…No other student characteristics significantly correlated with performance. These findings are consistent with previous research results on prior knowledge (McDonald and Stevenson, 1998;Stiller, 2003Stiller, , 2009Amadieu et al, 2009), intrinsic motivation (Fredericksen et al, 2000;Ali and Franklin, 2001;Aragon et al, 2001;Sankaran and Bui, 2001;Delialioglu, 2005;Waschull, 2005;Yukselturk and Bulut, 2007;Artino, 2008), computer attitude (Stiller, 2009, in press), and computer anxiety (Desai, 2001;Sam et al, 2005;Saadé and Kira, 2009;Hauser et al, 2012). The analyses of attitude toward computers and computer anxiety produced equivalent results, which reflects the redundancy of the measures as shown by the very high correlation between them.…”
Section: Discussing Theory and Previous Researchsupporting
confidence: 93%
See 2 more Smart Citations
“…No other student characteristics significantly correlated with performance. These findings are consistent with previous research results on prior knowledge (McDonald and Stevenson, 1998;Stiller, 2003Stiller, , 2009Amadieu et al, 2009), intrinsic motivation (Fredericksen et al, 2000;Ali and Franklin, 2001;Aragon et al, 2001;Sankaran and Bui, 2001;Delialioglu, 2005;Waschull, 2005;Yukselturk and Bulut, 2007;Artino, 2008), computer attitude (Stiller, 2009, in press), and computer anxiety (Desai, 2001;Sam et al, 2005;Saadé and Kira, 2009;Hauser et al, 2012). The analyses of attitude toward computers and computer anxiety produced equivalent results, which reflects the redundancy of the measures as shown by the very high correlation between them.…”
Section: Discussing Theory and Previous Researchsupporting
confidence: 93%
“…Viewed from this perspective, the level of prior knowledge can be connected to learning success. In the context of distance and online learning, which are more complex learning environments than has been investigated against the background of CLT, studies have reported that domain-specific prior knowledge is positively related to various measures of performance (e.g., McDonald and Stevenson, 1998;Stiller, 2003Stiller, , 2009Amadieu et al, 2009).…”
Section: Stiller and Bachmaier Cognitive Loads In Distance Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the disadvantages of having less prior knowledge might influence a learner's decision to drop out when negotiating the learning content. In the context of complex learning environments, including online learning scenarios, the level of domain-specific prior knowledge is known to consistently influence program usage, information processing and performance (Amadieu, Tricot, & Mariné, 2009). Studies from hypertext research have reported the positive impact of prior knowledge on various performance measures (e.g., Amadieu et al, 2009;McDonald & Stevenson, 1998;Stiller, 2003Stiller, , 2009Stiller, , 2015b).…”
Section: Domain-specific Prior Knowledgementioning
confidence: 99%
“…In the context of complex learning environments, including online learning scenarios, the level of domain-specific prior knowledge is known to consistently influence program usage, information processing and performance (Amadieu, Tricot, & Mariné, 2009). Studies from hypertext research have reported the positive impact of prior knowledge on various performance measures (e.g., Amadieu et al, 2009;McDonald & Stevenson, 1998;Stiller, 2003Stiller, , 2009Stiller, , 2015b). However, non-significant correlations were found when the courses were aimed at mastery learning (e.g., Stiller & Köster, manuscript submitted for publication).…”
Section: Domain-specific Prior Knowledgementioning
confidence: 99%